Genome-wide profiling of tRNA modifications by Induro-tRNAseq reveals coordinated changes - Yuko Nakano; Howard Gamper; Henri McGuigan; Sunita Maharjan; Jiatong Li; Zhiyi Sun; Erbay Yigit; Sebastian Grünberg; Keerthana Krishnan; Nan-Sheng Li; Joseph A. Piccirilli; Ralph Kleiner; et al. (Nature Communications)
Abstract While all native tRNAs undergo extensive post-transcriptional modifications as a mechanism to regulate gene expression, mapping these modifications remains challenging. The critical barrier is the difficulty of readthrough of modifications by reverse transcriptases (RTs). Here we use Induro—a new group-II intron-encoded RT—to map and quantify genome-wide tRNA modifications in Induro-tRNAseq. We show that Induro progressively increases readthrough over time by selectively overcoming RT stops without altering the misincorporation frequency. In a parallel analysis of Induro vs. a related RT, we provide comparative datasets to facilitate the prediction of each modification. We assess tRNA modifications across five human cell lines and three mouse tissues and show that, while the landscape of modifications is highly variable throughout the tRNA sequence framework, it is stabilized for modifications that are required for reading of the genetic code. The coordinated changes have fundamental importance for development of tRNA modifications in protein homeostasis.